SHIFTS IN MICROBIAL COMMUNITY STRUCTURE COULD BE LINKED TO WEATHER ANOMALIES? A CASE STUDY ON CACHAÇA (SUGARCANE DISTILLED SPIRIT) FERMENTATION - Portugal, Cauré Barbosa; da Cruz, Sandra Helena; Andreote, Fernando Dini (REVISTA DE AGRICULTURA, 2020)
Weather anomalies like high temperatures combined to long drought periods have frequently coincided with sluggish and spoiled fermentations in Brazilian cachaça distilleries. In this study, we compared the beginning of spontaneous fermentation in local processes to figure out which factors are distinctive and might be influencing fermentation in consecutive years with different weather conditions. We assessed two producing units in Southeast Brazil in 2013-2014, and daily analyzed two cases of spontaneous fermentation, considering molecular profile and the dynamics of microbial communities, as well as physicochemical parameters of the medium. Weather data were also collected. Atypical microbial community shifts and dominance of spoilage microorganisms were observed in 2014. The sugarcane juice also presented lower concentration of assimilable nitrogen in 2014 in association to lower ethanol yield. Compared to the last 20-year average, the rainfall was 7.5 times lower, in addition to general elevation of temperature (+ 3°C). Those bioprocesses influenced by lengthy droughts and higher temperatures disclose microbial communities defined by dominance and persistence of less demanding yeasts and overgrowth of bacterial populations. Also, the lack of nitrogen sources seems to be one of the major causes of biomass yield reduction, lagging sugar consumption by yeasts, and consequent spoilage activity.